EFFECTS OF PHYSICAL ACTIVITY ON BONE HEALTH: INVESTIGATE HOW DIFFERENT TYPES OF EXERCISE INFLUENCE BONE DENSITY AND STRENGTH - JAN , RU; KHAN , F; AFRIDI , MA; ISHAQ, S; KHATTAK , HE; SHAH , SGS (Biological and Clinical Sciences Research Journal, 2023)
This review study investigated the impact of various types of exercise on bone density and strength among individuals at LRH Peshawar between January 2023 and June 2023. Physical activity is a cost-effective and readily available modifiable factor significantly contributing to bone health. Given that nearly half of an adult’s bone mass is accrued during adolescence, exercise is incredibly beneficial. This paper reviews the most recent research to determine the optimal exercise components for enhancing bone strength and density. While walking alone may not increase bone mass, it can attenuate bone loss. Weight-bearing exercises must achieve the requisite mechanical intensity to generate a significant ground reaction force to be effective. This review examines the impact of exercise on bone density and strength.